Best mode of inspiratory muscle training in heart failure patients: a systematic review and meta-analysis. (November 2018) - Sadek, Zahra; Salami, Ali; Joumaa, Wissam H; Awada, Charifa; Ahmaidi, Said; Ramadan, Wiam
Objectives: The objective of this study was to evaluate the effects of inspiratory muscle training on inspiratory muscle strength, functional capacity and dyspnoea for patients with chronic heart failure, by summarising the published research on the effects of inspiratory muscle training. To identify the best mode of intervention in terms of: the load of maximal inspiratory pressure; the frequency of sessions; and the total duration of intervention. Methods: A relevant literature research using the PubMed database, Cochrane and references of published studies, from 1998 to 2016, was conducted. Out of 65 randomised controlled trials, seven were considered as potentially relevant and were retrieved for detailed analysis. The methodological quality of each randomised controlled trial was rated using the physiotherapy evidence database scale. Results: The included seven studies contained data on 203 patients. Typical training protocols involved training three, six or seven times per week with intensity ranging from 30% to 60% and for a duration ranging from 6 to 12 weeks. Maximal inspiratory pressure, walking distance and dyspnoea were improved in all studies and especially in those who set a load of 60% in their maximal inspiratory pressure, and have trained patients six times per week for 12 weeks. Conclusion: In chronic heart failure patients, inspiratory muscle training results in a marked improvement in inspiratory muscle strength, walking distance and dyspnoea, notably when training patients at 60% of maximal inspiratory pressure, six times per week and for 12 weeks. A small number of studies and heterogeneity among studies may limit the findings of the present study.